Design of 2x1 MIMO Microstrip Antenna Using Slit and Inset Technique For 5G Communication - Fahrul Solehudin; Zikra Aulia Sanaz; Syah Alam; Lydia Sari; Indra Surjati (Universitas Medan Area, 2021)
The fifth generation (5G) technology offers high speed communication systems and requires a multi input and multi output (Multiple Input Multiple Output / MIMO) antenna system to increase customer capacity. This research proposes a microstrip antenna design for a fifth-generation (5G) communication system that works at a frequency of 3.5 GHz. The antenna was designed using the RT-Duroid R5880 substrate type with dielectric constant (εr) = 2.2, thickness (h) = 1.57 mm and loss tan (tan α) = 0.0009. To produce optimal parameter, the antenna is optimized using slit on the edge with a total of 2 pairs. The addition of an inset aims to reduce the reflection coefficient of the proposed antenna. From the simulation results, the reflection coefficient value is -25 dB at a frequency of 3.5 GHz with a bandwidth of 220 MHz. The gain of the proposed antenna is 10 dB at a frequency of 3.5 GHz. The isolation coefficient obtained is -70 dB with a distance between (d) = 43 mm. The application of the MIMO antenna increases the gain by 49.52% compared to the single element microstrip antenna.